PHRASEOLOGICAL PICTURE OF THE WORLD AS MEANS TO DESCRIBE REALITY - Muradullaevna, Normuradova Gulnora (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
The article deals with the problem of the world phraseological picture as a linguistic phenomenon of the national and cultural development. It is possible to represent the ethnic and cultural characteristics of the linguistic world picture and create a holistic image of the ethnos reality, using the example of the Uzbek and English world phraseological picture, which acts as a means of the connection between the world picture and language, as a part of a global world picture, a stereotype of a certain people behavior.